The needs of freelancers and the characteristics of 'gigs': Creating beneficial relations between freelancers and their hiring organizations [version 1; peer review: 2 approved] - Melody Barlage; Arjen van Witteloostuijn; Arjan van den Born (Emerald Publishing, 2019)
More and more workers in Western economies are operating as freelancers in the so-called 'gig economy', moving from one project-or gig-to the next. A lively debate revolves around the question as to whether this new employment relationship is actually good for innovation in the 21st century economy. Proponents argue that in this gig process valuable knowledge is created and transferred from one organization to the next via freelancers through their sequence of temporary gigs or projects. Antagonists reason that freelancers are only hired as one-trick ponies on a transactional basis, where knowledge is neither created nor shared. In this study, we focus on the characteristics of gigs. Which project characteristics lead to increased engagement of freelancers, and hence to knowledge-sharing behavior? Our study suggests that the gig economy can indeed lead to increased knowledge sharing by and engagement of freelance workers, provided that organizations and freelancers structure and shape gigs in such a way that they: (1) not only suit the task requirements at hand and (2) fit with the acquired skills of the freelancer, but that these gigs also (3) leave ample of room for the freelancer's individual growth and development of new skills. This suggests that innovative organizations will need to shape gigs in such a way that freelancers are not only hired for their expertise, but rather that gigs also provide a learning opportunity for freelancers.